Analysis of The Influence of Perceived Compatibility, Perceived Ease of Use and Perceived Usefulness on Intention to Use Mobile Banking Digital Transaction Services of Banking Customers - Nurhasanah, Nurhasanah; Launtu, Ansir; Dharmawan, Donny; Ekasari, Silvia; Puwanti (SEULANGA SYSTEM PUBLISHER, 2023)
Among Asian nations, Indonesia is ranked fifteenth for internet usage. There are currently over two million mobile application subscribers of the bank taken in this study, a 80% rise since the beginning of 2021. The purpose of this study is to ascertain the degree to which consumer decisions about mobile banking are influenced by the Technology Acceptance Model (TAM) hypothesis. Descriptive analysis with a quantitative approach is used in this study. Utilizing the dimensions and indicators of each variable, data analysis is performed by determining the degree to which the independent variables—perceived ease of use, perceived usefulness, perceived risk, and perceived compatibility—have an impact on the dependent variable, or consumer decisions. Multiple regression analysis is used in this work. Because of the study's noteworthy findings, Ha is accepted and H0 is denied. The findings indicated that the decision to utilize mobile banking is somewhat influenced by perceived ease of use. The decision to adopt mobile banking is influenced in part by perceived utility. One factor influencing the choice to adopt mobile banking is perceived risk. The choice to utilize mobile banking is somewhat influenced by perceived compatibility. The choice to utilize mobile banking is simultaneously influenced by perceptions of compatibility, risk, utility, and convenience of use.